KAJIAN KOMUNITAS EKOR PEGAS (COLLEMBOLA) PADA PERKEBUNAN APEL (Malus sylvestris Mill.) DI DESA TULUNGREJO BUMIAJI KOTA BATU - Niwangtika, Widyarnes; Ibrohim, Ibrohim (Bioeksperimen: Jurnal Penelitian Biologi, 2017)
This research was conducted in order to determine composition, diversity, eveness, richness, important value index of springtail, and corellation between abiotic environment factor (temperature, pH and moisture) and diversity of springtail. Sampling was done using nilon sieve and pitfall trap, and this research was conducted in April-June 2014 in Tulungrejo village, Batu city. The result from this research, there are 11 species, 10 generas and 5 families of springtail. Diversity index of springtail both using nilon sieve and pitfall trap in apple plantation catagorized medium diversity. The result of important index value analyze showed that Entomobrya multifasciata has highest value. Based on regression analysis, abiotic factor has significant influence on diversity index of infauna.